ANALISA PARKIR PARAGON MALL SEMARANG - Mudjiastuti Handajani; Tut Wuri Handayani (Jurnal Teknik Sipil dan Perencanaan, 2016)
Pull traffic that occurs in complex Paragon Mall affect parking demand in these locations. For that we need research to obtain data - data that is requirsed by way of observations of drivers and parking attendants. The intent and purpose of this paper is to get the amount of traffic traveling tug toward Paragon Mall shopping complex and to determine parking demand at Paragon Mall shopping complex. Furthermore, based on the data that has been obtained so that data processing is done to obtain the desired result of which the accumulated maximum parking, towing trips, towing traffic, parking demand factors. From the calculation it is known that the maximum accumulation occurs on a Saturday, which is 173 to 295 types of automobiles and vehicle type motorcycle. Pull the whole trip occurred on Sunday at 4.76 people/100m2 Floor Area Groos. The amount of traffic tug Day on Saturday by 219 smp / hour for this type of car and 108 smp / hour for this type of motorcycle. Thus Paragon Mall has considerable pull the trip and have enough parking area where the number of plots for the car park as many as 260 plots for motorcycle parking and 800 parking plots.